2021
DOI: 10.1186/s12886-021-02079-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dorzolamide, benzalkonium-preserved dorzolamide and benzalkonium-preserved brinzolamide on selected biomarkers of oxidative stress in the tear film

Abstract: Background Long-term use of topical, especially benzalkonium chloride (BAC)-preserved, antiglaucoma medications can cause a negative impact on the ocular surface. The aim of the study was to assess the effect of topical carbonic anhydrase inhibitors (CAIs) on selected oxidative stress biomarkers in the tear film. Methods The patients were divided into four sex-matched groups: group C (n = 25) – control group – subjects who did not use topical antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…However, the aqueous layer of the TF, secreted by the lacrimal gland, contains various antioxidants, including ascorbic acid, lactoferrin, uric acid, and cysteine, which work in concert to protect the ocular surface against free radical injury ( Álvarez-Barrios et al., 2021 ). Additionally, lacrimal gland-secreted proteins, such as antioxidant enzymes including superoxide dismutase and GPX, make a contribution as antioxidants ( Sedlak et al., 2021 ). This machinery helps maintain the tear redox homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the aqueous layer of the TF, secreted by the lacrimal gland, contains various antioxidants, including ascorbic acid, lactoferrin, uric acid, and cysteine, which work in concert to protect the ocular surface against free radical injury ( Álvarez-Barrios et al., 2021 ). Additionally, lacrimal gland-secreted proteins, such as antioxidant enzymes including superoxide dismutase and GPX, make a contribution as antioxidants ( Sedlak et al., 2021 ). This machinery helps maintain the tear redox homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the active ingredients of the eye drops, preservatives used in eye drops, especially benzalkonium chloride (BAK), are shown to be a major cause of adverse reactions, and often a switch to preservative-free medication alleviates these symptoms [ 67 , 68 , 69 , 70 ]. Previous studies have highlighted that the prolonged use of these preservatives not only causes ocular surface inflammation but also induces oxidative stress in the tear film [ 71 , 72 ], further tipping off the balance of the ocular surface functions and increasing the risks of OSD development.…”
Section: Tear Fluid Proteomics In the Evaluation Of Therapeutic Outco...mentioning
confidence: 99%
“…5 Additionally, clinical studies conducted in humans have shown that the long-term use of solutions preserved with BAC is associated with abnormalities of tear film such as hyperosmolarity, instability, and increased oxidative stress. 5,6 An in vitro study conducted in canine corneal epithelial cells showed that BAC caused severe changes and inhibited migration of these cells at all concentrations tested. 7 The most common local adverse events associated with ocular NSAIDs are conjunctival stinging, burning, hyperemia, and corneal anesthesia, whereas corneal melting occurs in rare cases.…”
Section: Introductionmentioning
confidence: 99%
“…24 Several studies have reported abnormal oxidative stress status in various corneoconjunctival diseases in rabbits, mice, humans, cats, and dogs. 6,[24][25][26][27][28] The role of NSAIDs in oxidative status is controversial. [29][30][31] Additionally, no published studies have demonstrated the effects of ophthalmic NSAIDs on the oxidative stress status of the ocular surface in dogs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation